Validity of Diagnostic Codes and Liver-Related Laboratory Abnormalities to Identify Hepatic Decompensation Events in the Veterans Aging Cohort Study - Re, Vincent Lo (2011)
PURPOSE: The absence of validated methods to identify hepatic decompensation in cohort studies has prevented a full understanding of the natural history of chronic liver diseases and impact of medications on this outcome. We determined the ability of diagnostic codes and liver-related laboratory abnormalities to identify hepatic decompensation events within the Veterans Aging Cohort Study (VACS). METHODS: Medical records of patients with hepatic decompensation codes and/or laboratory abnormalities of liver dysfunction (total bilirubin ≥5.0 gm/dL, albumin ≤2.0 gm/dL, international normalized ratio ≥1.7) recorded one year before through six months after VACS entry were reviewed to identify decompensation events (i.e., ascites, spontaneous bacterial peritonitis, variceal hemorrhage, hepatic encephalopathy, hepatocellular carcinoma) at VACS enrollment. Positive predictive values (PPVs) of diagnostic codes, laboratory abnormalities, and their combinations for confirmed outcomes were determined. RESULTS: Among 137 patients with a hepatic decompensation code and 197 with a laboratory abnormality, the diagnosis was confirmed in 57 (PPV, 42%; 95% CI, 33% – 50%) and 56 (PPV, 28%; 95% CI, 22% – 35%), respectively. The combination of any code plus laboratory abnormality increased PPV (64%; 95% CI, 47% - 79%). One inpatient or ≥2 outpatient diagnostic codes for ascites, spontaneous bacterial peritonitis, or variceal hemorrhage had high PPV (91%; 95% CI, 77% – 98%) for confirmed hepatic decompensation events. CONCLUSION: An algorithm of 1 inpatient or ≥2 outpatient codes for ascites, peritonitis, or variceal hemorrhage has sufficiently high PPV for hepatic decompensation to enable its use for epidemiologic research in VACS. This algorithm may be applicable to other cohorts.